Do Smallholder Farmers Need Paddy Microtakaful Scheme? - Fauzilah Salleh; Nor Mazlina Abu Bakar; Nur Salina Ismail; Norfadzilah Rashid; Wan Jemizan Wan Deraman (Universitas Pasundan, 2023)
Smallholder farmers play a crucial role in the agricultural sector of developing nations, but they are exposed to a number of risks that could result in sizable financial losses. As an alternative risk-sharing mechanism that can assist smallholder farmers in effectively managing their risks, microtakaful has been introduced. The article intends to propose the Paddy Microtakaful Scheme (PMTS) exclusively for smallholding farmers in Malaysia. This protection is significant for smallholder farmers to provide sustainable economic growth and food security. A few key areas must be observed to understand the necessity of having the scheme. An overview of Malaysia’s agriculture sector is presented focusing on land use, employment, and production of food crops among the smallholder farmers. Risks and perils in agriculture, including natural disasters, pests, and crop diseases, are also outlined. The role of PMTS is also discussed, highlighting its many benefits to smallholder farmers. A survey was carried out among 275 smallholder farmers to gain information on their demographic profiles, farming activities as well as their willingness to contribute to the PMTS. The information is vital in developing a suitable and well-accepted PMTS, specifically among smallholder farmers in Malaysia. The PMTS framework presented in this report is based on a hypothetical product that contains four main attributes: 1) types of crops to be insured, 2) type of coverage, 3) contribution or the price, and 4) sum assured/benefit. The scheme includes coverage for natural disasters, pests, and crop diseases with the ultimate objective to reduce the vulnerability of the global food system. Further research will consist of the execution of a pilot program formulated to evaluate the effectiveness of PMTS. With the government’s three-way coordination and active roles, the smallholder farmers and Takaful company will become the essential constituents in realizing the PMTS.